Organizational dynamics and aggregate fluctuations: The role of financial relationships - Keisuke Otsu; Masashi Saito (University of Kent, School of Economics, 2011)
This paper constructs a dynamic stochastic general equilibrium model in which labor reallocations between production and organizational tasks generate endogenous TFP movements and also amplify and propagate the effects of exogenous shocks on macroeconomic activity. Organizational tasks in our model enhances financial relationships between firms and lenders, which lowers the credit spread. We calibrate and estimate the model using Japanese data and conduct a quantitative analysis. Our results suggest that the labor reallocation channel considered in this paper contributes greatly to the observed movements in the measured TFP, and serves as a quantitatively important amplification and propagation mechanism in aggregate fluctuations.
Keywords: E13; E32; 330; labor reallocations; financial relationship; organizational capital; TFP; aggregate fluctuations